A note on the effects of degeneracy on cost coefficients ranges and an algorithm to resolve interpretation problems - Gerhard Knolmayer (Universität Kiel, Institut für Betriebswirtschaftslehre; ZBW – Leibniz Information Centre for Economics, 1982)
The problems of determining meaningful dual values and of per-forming meaningful sensitivity analysis in degenerate optima are reconsidered. For primal degenerate optima, earlier results on determining meaningful dual values are used to propose an effi-cient algorithm for determining meaningful cost coefficient ranges. It is further shown that the recently proposed determi-nation of cost ranges at dual degenerate optima does not corres-pond to the usual definition of cost ranges.
Keywords: 650; Linear Programming and Sensitivity Analysis